2023
DOI: 10.1038/s41467-023-39884-6
|View full text |Cite
|
Sign up to set email alerts
|

Generation of out-of-plane polarized spin current by spin swapping

Abstract: The generation of spin currents and their application to the manipulation of magnetic states is fundamental to spintronics. Of particular interest are chiral antiferromagnets that exhibit properties typical of ferromagnetic materials even though they have negligible magnetization. Here, we report the generation of a robust spin current with both in-plane and out-of-plane spin polarization in epitaxial thin films of the chiral antiferromagnet Mn3Sn in proximity to permalloy thin layers. By employing temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The change in amplitude for the symmetric part is also observed for the device measured in Fig. 2e, which indicates the presence of out-of-plane field-like torque in the system 36,37 but it was absent in devices with other thicknesses. The STFMR measurements were also performed on the devices fabricated along the b-axis (current flows along the b-axis) of TaIrTe 4 , the representative curves are shown in Fig.…”
supporting
confidence: 58%
“…The change in amplitude for the symmetric part is also observed for the device measured in Fig. 2e, which indicates the presence of out-of-plane field-like torque in the system 36,37 but it was absent in devices with other thicknesses. The STFMR measurements were also performed on the devices fabricated along the b-axis (current flows along the b-axis) of TaIrTe 4 , the representative curves are shown in Fig.…”
supporting
confidence: 58%
“…[ 24,26 ] However, recent experimental findings challenge this interpretation by suggesting that the out‐of‐plane spin polarization is not associated with the chiral spin texture but rather arises due to spin scattering at the interface between the noncollinear antiferromagnetic thin film and the ferromagnetic layer. [ 40,48 ] We speculate that the inconsistent results observed could potentially be attributed to variations in sample quality. In comparison, we have identified three common features among the results that indicate σ z (or ξ z ) originating from the interface rather than the bulk: 1) The σ z spin current primarily corresponds to the field‐like torque rather than the damping‐like torque (i.e., SFLZADLZ$S_{FL}^Z \gg A_{DL}^Z$); 2) V mix exhibits changes in amplitude while maintaining the same sign when rotating ϕ H by 180° in angle‐dependent ST‐FMR measurements (i.e., the contribution of σ z to V mix is not strong enough to break the symmetry relation); 3) None of the results demonstrate deterministic perpendicular magnetization switching using a noncollinear antiferromagnet as the spin source.…”
Section: Spin‐orbit Torque Driven Magnetization Switchingmentioning
confidence: 99%
“…However, research on the SOT effect in Mn 3 Sn/ferrimagnet heterostructures is still limited, and unclear physical mechanisms remain, such as 1) the accurate determination of the spin diffusion length in noncollinear antiferromagnetic Mn 3 Sn material, 2) the role of self‐generated spin current in the electrical manipulation of noncollinear antiferromagnetic state, particularly in polycrystalline samples, [ 34,38 ] 3) the thermal contribution to electrical manipulation of noncollinear antiferromagnetic state, particularly in thick samples, [ 35,36 ] and 4) the origin of out‐of‐plane polarized spin current either from chiral spin texture or spin swapping at the interface. [ 39,40 ] All of the above controversies highlight the importance of understanding the material properties of Mn 3 Sn as a precondition for any analysis of the SOT effect due to its unique spin texture. Moreover, regarding potential applications, it is noteworthy that only a few studies have reported on the all‐electrical control of perpendicular magnetization switching utilizing Mn 3 Sn as the spin source.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many researches have reported the large SOT efficiency in metallic AFMs, which generally originate from the strong spin-orbit coupling effect. [6][7][8][9][10][11] In addition, many fascinating characteristics were also observed, for instance, anisotropic or anomalous SOT in the epitaxial grown IrMn, [12,13] generation of out-of-plane spin polarization in noncollinear AFMs, [14][15][16][17][18] field-free magnetization switching in AFM/FM structures due to the exchange bias. [19][20][21][22] To better employ the metallic AFMs in magnetization switching, it is crucial to quantitatively characterize the SOT efficiency.…”
mentioning
confidence: 98%